The Role of Labour Market Expectations and Admission Probabilities in Students' Application Decisions on Higher Education: the case of Hungary - Julia Varga (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2003)
This paper analyses the effects of labour market expectations and admission probabilities on students' application strategies to higher education. The starting hypothesis of this study is that students consider the expected utility of their choices, a function of expected net lifetime earnings and the probability of admission. Based on a survey carried out among Hungarian secondary school students, three aspects of application decisions are investigated: the number of applications; the institutions/ field specialisation ranked first and last in students' choices; and the selection between state-funded and cost-priced education. The results of this paper confirm that both expected wages and admission probabilities determine students' application strategies and that the seemingly irrational student preferences for institutions/orientations with less favourable labour market opportunities might be the result of a rational decision process.
Keywords: I20; J24; 330; Education; Human Capital; Skills; Occupational Choice; Labor Productivity